Inovação na Terapêutica Anticoagulante - Sofia Ramos; Sofia de Oliveira Martins (Revista Portuguesa de Farmacoterapia, 2013)
Introdution: Atherothrombosis and venous thromboembolism are the leading causes of morbidity and mortality. Anticoagulant therapy is crucial to decrease these factors by preventing the clotting of blood. Objective: Describe some of the new anticoagulant drugs, introduced in an attempt to overcome the limitations of traditional anticoagulant drugs (heparins, warfarin and acenocumarol). Method: Narrative literature review of relevant scientific articles published between 2006 and 2012. Results: A new strategy for the design of new antithrombotic drugs is based on selective inhibition of a specific coagulation factor, with potential to be more effective, safe and easy to use. These include direct thrombin inhibitors (dabigatran, bivalirudin, desirudin, lepirudin and argatroban) and factor Xa inhibitors (otamixaban, rivaroxaban, o apixaban, edoxaban and fondaparinux). Also, a new vitamin K antagonist has been developed, tecarfarin. This does not present the same limitations as the other, which is due essencially to the fact that is not metabolized by CYP450 enzymes. Conclusion: Anticoagulant therapy has been the target of an intense review so that its use in the clinical practice becomes indeed innovative and revolutionary. Currently, in Portugal, only fondaparinux, the dabigatran etexilate and rivaroxaban have been approved and commercialized.